Western’s War: A Study of an Ontario Canadian Officers’ Training Corps Contingent, 1939-1945 - Theobald, Andrew (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
The Second World War activities of the University of Western Ontario Canadian Officers’ Training Corps (COTC) provide an ideal case study that examines the influence of military demands on academic requirements, explores the experiences of part-time student soldiers, illuminates officer training and selection, and questions the effectiveness of the COTC at the most crucial stage in its history. The focus on Western highlights southern Ontario history, as the training unit encompassed Western’s main campus, the medical school, smaller London institutions like Huron College, and the Windsor (Assumption) and Waterloo affiliate colleges. These findings can also be compared and contrasted with the experiences of other post-secondary institutions.